Reconfiguring Global Development Pathways: Assessing The Strategic Role Of Digital Transformation In Advancing Inclusive And Sustainable Economic Growth - Runa Wiandara; Hafizah Muslimah (CV. SINAR HOWUHOWU, 2025)
The accelerating wave of digital transformation has reshaped global development trajectories, compelling governments, industries, and multilateral institutions to recalibrate strategies for achieving inclusive and sustainable economic growth. This study examines how digital innovations—ranging from data-driven governance and fintech ecosystems to digital entrepreneurship and smart industrial systems—serve as catalytic enablers of equitable development across diverse economic contexts. Drawing on cross-country evidence, the analysis demonstrates that digital transformation contributes to productivity enhancement, expanded market access, and improved public-service delivery, while simultaneously presenting structural risks such as digital exclusion, cybersecurity vulnerabilities, and uneven technological diffusion. The findings highlight that developing economies with strong institutional frameworks, adaptive regulatory policies, and coordinated multi-stakeholder partnerships are better positioned to leverage digital technologies for long-term sustainability. Ultimately, this research underscores the need for integrated digital strategies that align technological advancement with social equity and environmental resilience, ensuring that digital growth pathways translate into shared prosperity.